ALAT PEMBERSIH KARPET 3 IN 1 SEMI OTOMATIS UNTUK MESJID AL RIDHO SUNGAILIAT - Aan Febriansyah; Dinda Tania Pasha; Hafidz Fikri (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2022)
The COVID-19 pandemic has spread and has an impact on the fabric of life in all corners of the world and aspects of people's lives. No exception places of worship, especially mosques. The cleanliness of the carpet or floor is a must so that the worship process in the mosque is safe and comfortable. The cleaning process is usually carried out by mosque staff using a vacuum and sprayed with disinfectant/perfume. To assist and simplify the work of the cleaning staff, a 3 in 1 Semi-Automatic Carpet Cleaning Tool was designed (Dust Vacuum, Disinfectant Spray/Deodorizer and Dryer). This tool works automatically to clean dust, spray disinfectant/perfume and dry it according to the area of ??the mosque. This tool uses ultrasonic sensors to detect the state of the surrounding room. The L298N driver functions to control the speed and rotation of the DC motor so that the wheels can move straight based on the controller program using Arduino Uno, so that the robot moves straight and constant without hitting the wall. From the test results of the tool, it is found that the robot can suck dust, spray perfume/disinfectant and dry it with a robot speed of ± 10 meters/minute in a straight line with a carpet thickness of 0.5 cm.